Bacteria Energy Recovery System Using Natural Soil Bacteria in Microbial Fuel Cells - Nathaniel Brochu; Benjamin Belanger-Huot; Dmytro Humeniuk; Lingling Gong; Mehran Abbaszadeh Amirdehi; Jesse Greener; Amine Miled (Energies, 2021)
This paper describes a two-cycle bacteria energy recovery system (BERS) to power two embedded sensors: an ultra-low portable pH sensor and a sound sensor. The designed unit can handle up to seven microbial fuel cells (MFCs) to charge a super-capacitor. This allows the BERS to provide a constant 0.14 mW without further electrical components for signal conditioning. The two cycles were driven with a 100 k<semantics>Ω</semantics> load and a 10 Hz frequency. The BERS is also self-powered with an integrated start-up unit to be self-activated when the MFCs charge the energy-storing unit after three days. The BERS powered pH sensor has an error below 5% at 25 <semantics>∘</semantics>C and is able to work continuously while being activated for 4 h. The performances of the pH and sound sensors were determined based on a compromise between accuracy and power consumption.